A review on conventional and novel materials towards heavy metal adsorption in wastewater treatment application - Chai, Wai Siong; Cheun, Jie Ying; Kumar, P. Senthil; Mubashir, Muhammad; Majeed, Zahid; Banat, Fawzi; Ho, Shih-Hsin; Show, Pau Loke (Journal of cleaner production, 2021)
Wastewater treatment remains a critical issue globally till date despite various technological advancements and breakthroughs. Heavy metal in wastewater poses a great threat to human health if untreated properly, which makes its removal of utmost importance. Among various wastewater treatment techniques, adsorption is the most common technique to remove heavy metal in wastewater due to its flexible design, operation, and cost-effectiveness. Activated carbon being the most conventional adsorbent to remove heavy metal ion in wastewater owing to its microporous structure and ease of surface functionalization. However, the activated carbon separation from wastewater solution has been difficult and its high cost have prohibited its wide usage. Recently, the emergence of different novel materials has also showed their competitiveness in heavy metal ion removal. These promising novel materials exhibit several excellent attributes, for example large surface area, great mechanical strength, and high chemical inertness. This paper presents a brief review on the use, theory and future perspectives of conventional, as well as novel materials towards heavy metal adsorption in wastewater treatment application. [Display omitted] •Adsorption is most common technique for heavy metal removal in wastewater treatment.•Activated carbon is the conventional adsorbent material.•Novel materials with high specific area are beneficial in heavy metal removal.•Usage of conventional and novel materials towards heavy metal removal are discussed.